Enzymic Approach to Eurythermalism of Alvinella pompejana and Its Episymbionts - Lee, Charles K. (American Society for Microbiology (ASM), 2008)
The equilibrium model, which describes the influence of temperature on enzyme activity, has been established as a valid and useful tool for characterizing enzyme eurythermalism and thermophily. By introducing K(eq), a temperature-dependent equilibrium constant for the interconversion between E(act), the active form of enzyme, and E(inact), a reversibly inactive form of enzyme, the equilibrium model currently provides the most complete description of the enzyme-temperature relationship; its derived parameters are intrinsic and apparently universal and, being derived under reaction conditions, potentially have physiological significance. One of these parameters, T(eq), correlates with host growth temperature better than enzyme stability does. The vent-dwelling annelid Alvinella pompejana has been reported as an extremely eurythermal organism, and the symbiotic complex microbial community associated with its dorsal surface is likely to experience similar environmental thermal conditions. The A. pompejana episymbiont community, predominantly composed of epsilonproteobacteria, has been analyzed metagenomically, enabling direct retrieval of genes coding for enzymes suitable for equilibrium model applications. Two such genes, coding for isopropylmalate dehydrogenase and glutamate dehydrogenase, have been isolated from the A. pompejana episymbionts, heterologously expressed, and shown by reverse transcription-quantitative PCR to be actively expressed. The equilibrium model parameters of characterized expression products suggested that enzyme eurythermalism constitutes part of the thermal adaptation strategy employed by the episymbionts. Moreover, the enzymes' thermal characteristics correspond to their predicted physiological roles and the abundance and expression of the corresponding genes. This paper demonstrates the use of the equilibrium model as part of a top-down metagenomic approach to studying temperature adaptation of uncultured organisms.